The diversity of vaginal microbiome in women infected with single HPV and multiple genotype HPV infections in China - Liu, Shufa; Li, Yuanyue; Song, Yuzhu; Wu, Xiaomei; Baloch, Zulqarnain; Xia, Xueshan (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction The human papillomavirus (HPV) is the leading cause of cervical cancer globally. However, its microbial composition and association with the types of HPV infection remain elusive. Methods This study was designed to characterize the vaginal microbiota of 53 HPV-infected and 16 normal women (control group) by using high-throughput sequencing with the Illumina platform. Results In this study, the five leading phyla were Firmicutes (73.9%), Actinobacteriota (12.8%), Proteobacteria (6.2%), Fusobacteria (3.5%), and Bacteroidota (3.1%). We found that single HPV genotype–positive women had higher α-microbial diversity compared with HPV-negative and multiple HPV–positive women. In women with a single HPV genotype infection, the HPV-16 infection had significantly higher α-diversity than other genotype infections. In multiple HPV genotype–positive women, the highest α-diversity was found in women positive for HR–HR HPV genotype infection, compared with other infections. Furthermore, in single- and multiple-genotype infections, the abundance of s_unclassified_g_Lactobacillus decreased whereas the abundance of s_Gardnerella_vaginalis increased compared with control. Additionally, s_unclassified_f_Rhizobiaceae and s_sneathia_sanguinegens were only found in HPV-infected women. Conclusion This study showed that the type of HPV infection was associated with the composition of the vaginal microbiota. Further studies on HPV genotypes and vaginal microbiota are necessary to uncover more mysteries of their association and provide a promising therapeutic target as well as low-cost future therapeutic strategies.